Pengaruh Promosi Media Sosial dan Celebrity Endorsement terhadap Minat Kunjungan Generasi Z pada Photobooth Photoism Indonesia: The Influence of Social Media Promotion and Celebrity Endorsement on Generation Z's Interest in Photoism Indonesia - Sharfina Fildzah; Ulta Rastryana; Rini Larasati Irawan (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effect of social media promotion (X1) and Celebrity Endorsement (X2) on the visit intention of Generation Z to Photoism Indonesia photobooth (Y), both partially and simultaneously. A quantitative method with purposive sampling was applied to 100 Generation Z respondents aged 17–29 who had been exposed to Photoism content on social media. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS 27. The t-test results show that social media promotion has a significant partial effect (t=5.487; Sig.=0.000), as does Celebrity Endorsement (t=4.294; Sig.=0.000). The F-test indicates a significant simultaneous effect (F=36.526; Sig.=0.000). An R Square of 0.430 indicates both variables explain 43% of the variation in visit intention. Social media promotion contributes more dominantly (25.40%) than Celebrity Endorsement (17.61%). These findings enrich digital marketing research in the experience-based creative industry.